PROFIL KRATIVITAS SISWA DALAM PENYELESAIAN MASALAH MATEMATIKA PADA MATERI SEGIEMPAT DITINJAU DARI GAYA KOGNITIF - Manurung, Ontang; Runtu, Patricia V J; Halean, Vine (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
ABSTRACT. This research was conducted to describe the creativity profile of eighth grade students of SMP Negeri 3 Tondano in solving mathematical problems in quadrilateral in terms of reflective and impulsive cognitive styles. This research is categorized as a descriptive study with a qualitative approach. This research was conducted at SMP Negeri 3 Tondano in odd semester 2019/2020. The subjects of this study were two eighth grade students who had reflective and impulsive cognitive styles. Data collection techniques in this study used tests and interviews, while data analysis techniques used data reduction, data presentation, drawing conclusions and verification. The results of data analysis showed that the reflective cognitive style subjects could meet the indicators of fluency, flexibility and novelty.Â Impulsive cognitive style subjects can meet the indicators of fluency, flexibility but do not meet the indicators of novelty. Thus it can be concluded that students with reflective cognitive styles and students with impulsive cognitive styles differ for the level of creative thinking abilities. The level of creative thinking ability in students with reflective cognitive style isÂ higher than impulsive cognitive style students.Keywords: Cognitive Style, Quadrilateral, Creativity